2020
DOI: 10.1002/tsm2.212
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes are present at human and murine myotendinous junctions

Abstract: The myotendinous junction (MTJ) has been subject to increasing interest during the past decade, and the unique properties of this region have been revealed. Several studies, mainly on animals, have shown that the most distal part of the sarcolemma is folded and that these foldings are surrounded by tendon. This architecture increases the interface area of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Osteocrin is produced by skeletal muscle (51), is responsive to exercise (52), and overexpression of osteocrin has been reported to prevent muscle atrophy in cachexic mice (53). Furthermore, osteocrin has been linked to browning of adipose tissue (54), which is potentially related to our recent observations of adipocytes at the muscle-tendon interface in human hamstring tissue (55). Together these studies suggest a role for osteocrin specifically in the domain of skeletal muscle fibers close to the MTJ.…”
Section: Discussionmentioning
confidence: 63%
“…Osteocrin is produced by skeletal muscle (51), is responsive to exercise (52), and overexpression of osteocrin has been reported to prevent muscle atrophy in cachexic mice (53). Furthermore, osteocrin has been linked to browning of adipose tissue (54), which is potentially related to our recent observations of adipocytes at the muscle-tendon interface in human hamstring tissue (55). Together these studies suggest a role for osteocrin specifically in the domain of skeletal muscle fibers close to the MTJ.…”
Section: Discussionmentioning
confidence: 63%
“…It has recently been demonstrated that adipocytes exist in high numbers in close relation to the MTJ in humans and mice (Figure 5; Jakobsen et al, 2020). Adipocytes in skeletal muscle is normally a sign of poor muscle function and insulin resistance (Vettor et al, 2009), but at the MTJ adipocytes are present in healthy humans and animals.…”
Section: Cell Turnovermentioning
confidence: 99%